Analisis Tingkat Kesehatan Koperasi Syariah - Yusuf, Burhanuddin (Faculty of Economic and Business, 2016)
Analysis of Islamic Cooperatives SoundnessThe purpose of this study is to investigate and assess the level of health Islamic financial services cooperatives as Islamic microfinance institutions and to measure its overall performance, so the sharia cooperative can continue to improve to improve its quality. This study uses qualitative and quantitative methods. This assessment tool is an adaptation of the method of CAMEL customized with a few extras such as aspects of sharia. The object of this study is a cooperative financial services BMT Sharia al Munawwarah. The findings from this study that the co-operative Financial Services Syariah BMT Al Munawwarah categorized as cooperative healthy enough. But there are some things that do not meet the criteria of soundness. Weaknesses that need to be improved on the aspects of sharia supervisory function, but can be addressed by improving the quality of human resources both supervisors, administrators and managers. Thus the assumption Cooperative sharia was unprofessional and not well manajemenya is the assumption that less preciseDOI: 10.15408/ess.v6i1.3124